Financial Feasibility Study and Development of Technical Specifications for Coffee Agroforestry for Community Forest Farmers with Revolving Fund Support for Productivity Optimization - Oktoyoki, Hefri; Pratama, Benny; Putra, Yusran Panca; Novrian, Willi; Douni, James Byeker; Ansiska, Paisal (Universitas Pattimura, 2024)
This research investigates coffee agroforestry systems' financial feasibility and technical specifications in community forests (HKm). Coffee agroforestry is acknowledged for its potential to enhance biodiversity, increase land productivity, maintain ecological balance, and provide economic benefits for small-scale farmers. The study employs a mixed-methods approach, utilizing in-depth interviews, field observations, and questionnaires to gather primary data while incorporating reports and literature as secondary data sources. The analysis reveals that the coffee agroforestry system in HKm demonstrates financial viability, with a positive NPV, a BCR exceeding 1, and an IRR of 33%. However, challenges such as insufficient technical knowledge and limited financial support persist as significant barriers. Furthermore, this research develops technical specifications, including selecting high-quality coffee seeds, shoot grafting techniques, fertilization, and pest management practices. These specifications are intended to serve as a practical guide for farmers adopting coffee agroforestry systems, enabling them to improve productivity and economic well-being. Moreover, the findings of this study provide a solid foundation for developing policies that encourage the widespread adoption of coffee agroforestry. As a result, this research makes notable contributions to both the scientific and practical aspects of coffee agroforestry for Community Forest farmers, paving the way for further research and formulating comprehensive strategies to address the challenges farmers face.